The Effect of Profitability and Company Age on Human Resource Accounting Disclosure in IDX-Listed Banking Companies - Destriyana Luthfiyanti; Erna Sulistyowati (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2025)
This study aims to examine the effect of profitability and firm age on human resource accounting disclosure (HRAD) in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. This study uses a quantitative approach with multiple linear regression based on secondary data obtained from company annual reports. The analysis results indicate that profitability does not significantly effect HRAD, while company age has a significant positive effect on HRAD. Simultaneously, both independent variables significantly effect HRAD, although their contributions in explaining HRAD variations remain limited. These findings imply that the operational age of a company is more relevant in encourage human resource information disclosure than financial performance. This study also highlights the importance of a company's experience and maturity in establishing more transparent non-financial reporting practices. However, the low coefficient of determination value indicates the need to include additional variables in future research to develop a more comprehensive model.